Catalytic role of the calcium ion in GH97 inverting glycoside hydrolase. Issue 17 (10th July 2014) - Okuyama, Masayuki; Yoshida, Takuya; Hondoh, Hironori; Mori, Haruhide; Yao, Min; Kimura, Atsuo
Abstract : The role of calcium ion in the active site of the inverting glycoside hydrolase family 97 enzyme, Bt GH97a, was investigated through structural and kinetic studies. The calcium ion was likely directly involved in the catalytic reaction. The pH dependence of k cat / K m values in the presence or absence of calcium ion indicated that the calcium ion lowered the p K a of the base catalyst. The significant decreases in k cat / K m for hydrolysis of substrates with basic leaving groups in the absence of calcium ion confirmed that the calcium ion facilitated the leaving group departure. Abstract : The crystal structure of EDTA‐treated Bt GH97a has a sodium instead of a calcium ion at the active site. The calcium ion stabilizes the deprotonated state of the base catalyst. The calcium ion assists the departure of the leaving group.